In Vitro Acaricidal Activity of Atropa belladonna and Its Components, Scopolamine and Atropine, against Rhipicephalus (Boophilus) microplus - R. Godara; M. Katoch; R. Katoch; Anish Yadav; S. Parveen; Bhavna Vij; Varun Khajuria; G. Singh; Nirbhay K. Singh (The Scientific World Journal)
In vitro efficacy of methanolic extract of Atropa belladonna and its components scopolamine and atropine was assessed against Rhipicephalus (Boophilus) microplus. Five concentrations of the extract (1.25%, 2.5%, 5%, 10%, and 20%) were used whereas scopolamine and atropine were each tested at 0.1%. In adult immersion test, the extract was lethal to ticks at 20% concentration. The LC50 and LC95 values were determined as 6.875% and 17.306%, respectively. The extract caused a significant reduction (P<0.05) in egg mass production at 10% concentration. In larval packet test, the extract was lethal to larvae in the concentrations of 10% and 20% after 24 h, with LC50 and LC95 values of 1.321% and 4.935%, respectively. Scopolamine and atropine showed 93.3% and 60.0% mortality of adult ticks, respectively, but they caused complete (100%) blocking of hatching as well as 100% larval mortality. Scopolamine and atropine were observed to be more potent than the crude extract at an equivalent concentration in both the bioassays.